Communicative Textbooks: English Language Textbooks in Iranian Secondary School - Dahmardeh, Mahdi (Linguistik Online, 2009)
English language teaching materials (textbooks) play an important role in many language classrooms, but recently there have been a lot of debates within the English language teaching profession based on the actual role that materials play in teaching English as a foreign language. Arguments have encompassed both the potential and the limitations of materials used for ’guiding’ students through the learning processes and curriculum as well as the needs and preferences of teachers who are using the textbooks that are available. Other issues that have arisen in recent years include textbook design and practicality, methodological validity, the role of textbooks in innovation, the authenticity of materials in terms of their representation of language, communicative textbooks, and balance in presenting the language skills as well as cultural components. The purpose of this article is to report the findings of a study carried out in 2006 into how Iranian textbooks could be made more communicative. The textbooks referred to are three English language textbooks, which are currently used in Iranian Secondary Schools. Although the work has been done within Iranian context, many suggestions could be applied to other foreign/second language situations. I will start my discussion by presenting an overview about the English language teaching in Iran, before and after the revolution. This will be followed by presenting the findings of this research that would include the Iranian ELT curriculum, the questionnaire survey (author’s and teachers’ perspectives as well as their discomfort will be addressed) as well as introducing the English language coursebooks for secondary schools in Iran (topic, progression, structure of the lessons, types of exercises etc.). I will then present a discussion on findings of this research which would be a detailed exemplary criticism and suggestions for changes to make the materials communicative. The findings of this explanatory case study revealed that there are many inconsistencies between the learners’ needs, and the textbooks that are available for learning and teaching the English language though a few of them are reliable. The purpose of this research project is to recommend constructive changes, in order to make the textbooks more communicative as well as compatible with the students’ and teachers’ needs and expectations.